Cell Death in Salivary Glands of Rhipicephalus (Boophilus) microplus (Canestrini, 1887) (Acari: Ixodidae) Females at Semi-engorged Feeding Stage - Nunes, Erika Takagi; Scopinho Furquim, Karim Christina [UNESP]; Bechara, Gervasio Henrique [UNESP] (Informa Healthcare, 2010)
The ultrastructure of the salivary glands of Rhipicephalus (Boophilus) microplus females is described during feeding. In beginning of feeding, individuals show acini I with many mitochondria and wide basal labyrinth in peripheral cells; glycoprotein granules only in b and c(3) cells (acini II); and epithelial interstitial cells with developed basal labyrinth between f cells (acini III). Semi-engorged females show cells in degeneration, with autophagic vacuoles, lysosomes, myelin figures, and irregular, condensed, and/or fragmented nuclei, in addition to apoptotic bodies. R. B. microplus points to apoptosis in these organs before the detachment from the host, in contrast to others tick species.</.